2015
DOI: 10.4049/jimmunol.1500055
|View full text |Cite
|
Sign up to set email alerts
|

CD11c-Expressing B Cells Are Located at the T Cell/B Cell Border in Spleen and Are Potent APCs

Abstract: Besides secretion of antigen-specific antibodies, B cells may play an important role in the generation of immune responses by efficiently presenting antigen to T cells. We and others recently described a subpopulation of CD11c+ B cells (Age/autoimmune associated B cells, ABCs) which appear with age, during virus infections and at the onset of some autoimmune diseases and which participate in autoimmune responses by secreting autoantibodies. Here we assessed the ability of these cells to present antigen and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
173
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(188 citation statements)
references
References 47 publications
12
173
0
Order By: Relevance
“…For example, early studies showed that ABCs obtained from aged animals can present antigen and tend to induce Th17 polarization (22). More recent findings extend these ideas and also suggest that ABCs obtained from aged or autoimmune mice process and present antigen more efficiently that other B cells (33). …”
Section: The Emergence and Characteristics Of Age-associated B Cellsmentioning
confidence: 70%
“…For example, early studies showed that ABCs obtained from aged animals can present antigen and tend to induce Th17 polarization (22). More recent findings extend these ideas and also suggest that ABCs obtained from aged or autoimmune mice process and present antigen more efficiently that other B cells (33). …”
Section: The Emergence and Characteristics Of Age-associated B Cellsmentioning
confidence: 70%
“…2c). These age/autoimmune‐associated B cells have been characterized elsewhere and will not be a primary focus of this study 17, 18, 19, 20. These data show that ageing is associated with significant dynamic changes to the frequency and number of certain B‐cell populations in the spleen.…”
Section: Resultsmentioning
confidence: 88%
“…/CD11c + B cell subset, called age-associated B cells, which has increased capacity to respond to TLR stimulation, present Ag, and secrete autoantibodies, accumulates in aged mice and also appears in mice with certain viral infections and autoimmune conditions (41)(42)(43). Several features of murine age-associated B cells are shared with human FCRL5 + TLM B cells, including reduced response to BCR and CD40 stimulation, accumulation in chronic viral infections and autoimmune conditions, and elevated expression of CD11c, MHC class II, CD80, CD86, CD95, and T-bet (42,44).…”
mentioning
confidence: 99%
“…Several features of murine age-associated B cells are shared with human FCRL5 + TLM B cells, including reduced response to BCR and CD40 stimulation, accumulation in chronic viral infections and autoimmune conditions, and elevated expression of CD11c, MHC class II, CD80, CD86, CD95, and T-bet (42,44). Nevertheless, this mouse subset harbors distinct attributes, including robust differentiation into Ab-secreting cells in response to combined TLR and BCR stimulation (41), elevated CCR7 expression that was proposed to lead to localization of the cells at the splenic T/B border (43), and uncompromised survival in culture independent of BAFF (41). It is not known whether TLM B cells accumulate with aging in humans.…”
mentioning
confidence: 99%